أشكال الأنا عند بشار بن برد وأثرها في خطابه الشعري: Forms of the Self (Ego) in Bashshar Ibn Burd and their Impact on His Poetic Discourse - Ghalyoun, Safaa Muhammad; Alosman, Abdulrahman (Al-Basirah Journal, 2025)
This critical study examines the forms of the “self” in the poetic discourse of Bashshar ibn Burd, beginning with the impact of blindness and the psychological disturbance it created in the poet’s perception of himself and of others. The research problem arises from the marked contradictions in Bashshar’s self-image, which oscillates between weakness and rebellion, pride and loss, thereby necessitating an inquiry into the psychological and social factors that contributed to the emergence of these divergent self-representations. The study aims to analyze the images of the self in Bashshar’s poetry and uncover their major manifestations, to clarify the impact of blindness and harsh life conditions on the formation of his poetic persona, and to interpret the relationship between the self and the other from a psychological and analytical perspective. The study adopts a psycho-analytical and textual approach, involving close reading of the poems and connecting them to the poet’s personal and social circumstances, in addition to analyzing the semantic and rhetorical structures that reveal the conflicts of the self and its shifting positions. The method of analysis consists of eliciting meaning from within the texts themselves and comparing them with biographical evidence, the surrounding cultural environment, and the intellectual tensions of the Abbasid period in order to explain the transformations of the self between submission and assertiveness. The findings show that the self in Bashshar’s poetry is not a fixed entity but a set of conflicting forms shaped by psychological factors -such as feelings of deficiency, repression, and compensation- and by social factors such as marginalization and low status, as well as by ethnic tensions between his Persian origin and Arab affiliation. The study reveals several distinct forms of the self: the broken self influenced by blindness, the proud and rebellious self that resorts to exaggeration to compensate for its deficiencies, and the fragmented self that reflects a crisis of identity. These contradictions, the study concludes, are not merely artistic phenomena but a direct reflection of the poet’s lived experience, his disputes, and his internal and external struggles.